Journal Economics, business & accountancy : MODEL OF IT ADOPTION FOR INCREASING THE MSME’S COMPETITIVE ADVANTAGE - Nurhadi (PPPM Perbanas, 2013)
In the emerging global market context, the adoption and use of information technology (IT) iswidely seen as critical for the competitiveness of Micro, Small and Medium Enterprises(MSMEs). This study aims to describe: the degree of IT adoption; the reasons to use IT; theinhibiting factor of IT adoption; and the pattern of IT adoption for MSMEs. This study is adescriptive research. The population is MSMEs registered in the Bag and Suitcases IndustryCooperative (INTAKO) Sidoarjo.